Digital literacy, low-code pedagogical ecosystems, and innovative teaching in primary education - Menik Miliyana; Fina Fakhriyah; Ahmad Hariyadi; Mohd Syakir Mohd Rusydi (Bulletin of Educational Management and Innovation, 2025)
Background: Digital transformation in elementary schools continues to advance alongside the increasing use of technology in learning. However, the presence of technology has not always been accompanied by the emergence of innovative teaching practices, as the mechanisms explaining the relationship between teachers’ digital literacy, the technological environment, and pedagogical competence are not yet fully understood. Purpose: This study aims to analyze the relationship between digital literacy, a low-code-based pedagogical ecosystem via microsites, Technological Pedagogical Content Knowledge (TPACK), and innovative teaching practices among elementary school teachers. Method: This study employed a quantitative explanatory survey involving 83 elementary school teachers in Jepara Regency, Indonesia, selected through proportional stratified random sampling. Data were collected using a structured questionnaire measuring digital literacy, low-code pedagogical ecosystems, TPACK, and innovative teaching practices. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed to examine the direct and indirect relationships among the proposed constructs. Findings: The findings reveal that digital literacy strongly promotes the use of low-code pedagogical ecosystems, which subsequently strengthen teachers’ TPACK competencies. TPACK emerged as the primary mechanism underlying innovative teaching practices, with significant indirect effects observed for Digital Literacy → TPACK → Innovative Teaching Practice (β = 0.231, p = 0.001), Low-Code Pedagogical Ecosystem → TPACK → Innovative Teaching Practice (β = 0.266, p < 0.001), and the sequential pathway Digital Literacy → Low-Code Pedagogical Ecosystem → TPACK → Innovative Teaching Practice (β = 0.167, p = 0.001). The proposed model explained 67.8% of the variance in innovative teaching practices (R² = 0.678). Moreover, Digital Literacy demonstrated a large effect on the Low-Code Pedagogical Ecosystem (f² = 0.649), while TPACK exerted the strongest effect on innovative teaching practices (f² = 0.702), confirming its central role in digital pedagogical transformation.